THE RELATIONSHIP BETWEEN QUALITY ASSURANCE AND THE FORMATION OF PROFESSIONAL QUALIFICATION OF MANAGERIAL STAFF IN THE HIGHER EDUCATION SYSTEM - Akbar Salimovich Djuraev , Faxriddin Toshtemirovich Esanboboyev , Umida Erkinovna Giyasova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article describes the influence of quality assurance on training of highly qualified managerial staff of higher education institution. The concept of quality reviewed from philosophical, social, economic, legal and other aspects. Such notions as quality management, quality control and quality assessment and their importance in modernization of education were considered in the paper. Functional responsibilities of higher education institution managers in ensuring the quality of education were given in details which determined the quality planning as one of the main functional tasks of higher education institution managerial staff in ensuring the quality of education. Conclusions and recommendations were also developed to improve education quality and quality of management in higher education.